Lichenophilous species of Epidamaeus and Spatiodamaeus from high mountains of Mongolia, with remarks on their ontogeny (Acari: Oribatida) - Bayartogtokh, Badamdorj; Burkitbaeva, Ulzhan D.; Enkhbayar, Tojoo (Zootaxa, 2016)
Herein, the description of the adults and immature instars of a newly discovered species, Epidamaeus munkhbayari sp. nov. along with detailed illustrations and data on habitat ecology are provided. Adults of this new species can be easily distinguished form other known species of Epidamaeus by the combination of following characters: two pairs of well-developed prodorsal ridges, the presence of ventral tubercles E2a, Va and Vp, the short, thin interlamellar setae, and the strongly developed tectum of podocephalic fossa. Further, the redescription of adults and morphology of deutonymph of a little known species, Spatiodamaeus cf. fageti Bulanova-Zachvatkina, 1957, which is recorded for the first time in Asia, are given. The diagnosis of the latter species is modified and enriched with the characters of deutonymph. Following the descriptions and comparisons, we discuss aspects of the distribution and ecology of both studied species. Comparative characteristics of juveniles of different species belonging to Epidamaeus and Spatiodamaeus are performed, and the extended discussion on the immature morphology of Damaeidae is provided. Based on the comparative analyses, it can be generalized that the juvenile morphologies of not only Epidamaeus and Spatiodamaeus, but also those of other genera of the family are very similar, and hence, they differ from one another only by a few features, such as the body size, length of setiform organs, such as sensilli, interlamellar as well as gastronotic setae, structure and location of gastronotic cornicles. Epidamaeus munkhbayari sp. nov. is currently known only from the type locality; S. fageti is a Palaearctic species, known from Central and Eastern Europe and Central Asia. Both species appear to be sylvicolous, and primarily inhabitants of lichens growing on tree trunks as well as bare rocks. A list of oribatid mites, inhabiting the lichens growing on tree trunks and bare rocks in a high mountain cool temperate forest together with the two species central to this study, is given.